The Use of Analytic Hierarchy Process (AHP) Method in Choosing the Best Tree Type for Industrial Plantations: The Case of Kastamonu Province - Şen, Gökhan; Güngör, Ersin (Turkish Journal of Forestry, 2018)
Industrial plantation Investments are very important for the closure of existing industrial wood product supply and for the conservation of natural forests and sustainable forest ecosystem management. Within this scope, the tree species selection was made to provide the most benefit from industrial plantation investments in the study. In the analysis, Analytic Hierarchy Process (AHP) method, which is one of the multi criteria decision making processes, is used. Economic, climatic, edaphic and physiological criteria and sub-criteria were evaluated in line with the opinions of public institutions, local residents and private sector representatives. In the evaluation made among the Maritime pine, cultivated populus “i214”, Turkish pine, eucalyptus, ash, duglas fir, alder and radiata pine. ash was determined as the first priority specie for industrial plantations. It is followed by radiata pine and maritime pine.
Keywords: industrial plantation; kastamonu; çok kriterli karar verme; multi criteria decision making; ahp; ahs; Mühendislik; Forestry; afforestation investment; SD1-669.5; Industrial plantation; Afforestation investment; Multi criteria decision making; AHP; Kastamonu; Turkey; Engineering; Çok kriterli karar verme; AHS; Kastamonu; Endüstriyel ağaçlandırmalar; Ağaçlandırma yatırımları; Turkey; turkey; ağaçlandırma yatırımları; endüstriyel ağaçlandırmalar; 15. Life on land